The Role of Islamic Bank Capital Structure and Performance in Promoting Price Stability in Indonesia - Agustina, Maulidar; Majid, M. Shabri Abd.; Zulkifli, Zulkifli; Pranata, Eka Octavian (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the impact of capital structure and financial performance of Islamic banks on price stability in Indonesia using an Autoregressive Distributed Lag (ARDL) model with quarterly data from 2014 to 2024. Key variables include the Capital Adequacy Ratio, Total Regulatory Capital, Tier 1 Capital, Risk-Weighted Assets, Net Income, and the Consumer Price Index. Long-term findings reveal that robust capital indicators enhance price stability by strengthening banks' resilience and credit capacity. In contrast, Net Income mitigates inflationary pressure in the long run but intensifies it in the short term. The error correction term confirms rapid adjustment toward equilibrium after short-term shocks. These results underscore the critical role of sound capital and profitability in reinforcing Islamic banks’ contribution to Indonesia’s monetary policy, offering valuable insights for policymakers and regulators in promoting macroeconomic stability.